Barriers and Facilitators to Health-Care Provider Payment Reform – A Scoping Literature Review - Ndayishimiye C; Tambor M; Dubas-Jakóbczyk K (Risk Management and Healthcare Policy, 2023)
Costase Ndayishimiye,1,2 Marzena Tambor,2 Katarzyna Dubas-Jakóbczyk2 1Doctoral School of Medical and Health Sciences, Jagiellonian University Medical College, Krakow, Poland; 2Health Economics and Social Security Department, Institute of Public Health, Jagiellonian University Medical College, Krakow, PolandCorrespondence: Costase Ndayishimiye, Doctoral School of Medical and Health Sciences, Jagiellonian University Medical College, ul. św. Łazarza 16, Krakow, 31-530, Poland, Tel +48579143137, Email costase.ndayishimiye@doctoral.uj.edu.plBackground: Changes to provider payment systems are among the most common reforms in health care. They are important levers for policymakers to influence the health system performance. The aim of this study was to identify, systematize, and map the existing literature on the factors that influence health-care provider payment reforms.Methods: A scoping review was conducted. Literature published in English between 2000 and 2022 was systematically searched in five databases, relevant organizations, and journals. Academic publications and grey literature on health-care provider payment reform and the factors influencing reform were considered. An inductive thematic analysis was applied to map the barriers and facilitators that influence payment reforms.Results: The study included 51 publications. They were divided into four categories: empirical studies (n=17), literature reviews (n=6), discussion/policy papers (n=18), and technical reports/policy briefs (n=9). Most of the studies were conducted in developed economy countries (n=36). The most frequently reformed payment method was fee-for-service (n=37), and the newly implemented methods included bundled payments (n=16), pay-for-performance (n=15), and diagnosis-related groups (n=11). This study identified 43 sub-themes on barriers to provider payment reforms, which were grouped into eight main themes. It identified 51 sub-themes on facilitators, which were grouped into six themes. Barriers include stakeholder opposition, challenges related to reform design, hurdles in implementation structures, insufficient resources, challenges related to market structures, legal barriers, knowledge and information gaps, and negative publicity. Facilitators include stakeholder involvement, complementary reforms/policies, relevant prior experience, good leadership and management of change, sufficient resources, and external pressure to introduce reform.Conclusion: The factors that influence health-care payment reforms are often contextual and interrelated, and encompass a variety of perspectives, including those of patients, providers, insurers, and policymakers. When planning reforms, one should anticipate potential barriers and devise appropriate interventions.Registration: The study was registered with the Open Science Framework.Keywords: barriers, facilitators, health care provider, health reform, payment reform